2017
DOI: 10.1093/jee/tow298
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics ofBuzura suppressaria(Lepidoptera: Geometridae) Assembled De Novo Yield Insights Into Response AfterBuzura suppressariaNuclear Polyhedrosis Virus Infection

Abstract: Buzura suppressaria Guenee (Lepidoptera: Geometridae) is a defoliator that seriously harms eucalyptus trees in South China. Buzura suppressaria nuclear polyhedrosis virus (BsNPV) is a baculovirus that infects B. suppressaria with high specificity and efficiency. Transcriptomes of B. suppressaria were sequenced before and after BsNPV infection using an Illumina-based platform to probe for differentially expressed genes (DEGs) of B. suppressaria after viral infection. On average, ∼57.4 million high-quality clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Sample RNA was extracted by applying the TRIzol method, and the cDNA library was analyzed by using sequencing-by-synthesis technology with the Illumina HiSeq high-throughput sequencing platform [7] (Hidehiro et al, 2017). The obtained high-quality reads were then analyzed bioinformatically using a 2100 Bioanalyzer (Agilent), and functional annotation was carried out by comparing the unigenes with the GO and KEGG databases [8] (Luo et al, 2017).…”
Section: Transcriptomic Sequencingmentioning
confidence: 99%
“…Sample RNA was extracted by applying the TRIzol method, and the cDNA library was analyzed by using sequencing-by-synthesis technology with the Illumina HiSeq high-throughput sequencing platform [7] (Hidehiro et al, 2017). The obtained high-quality reads were then analyzed bioinformatically using a 2100 Bioanalyzer (Agilent), and functional annotation was carried out by comparing the unigenes with the GO and KEGG databases [8] (Luo et al, 2017).…”
Section: Transcriptomic Sequencingmentioning
confidence: 99%
“…22 Recently, RNA sequencing (RNA-Seq) has been widely used in the study of insect stress response, and this technique has emerged as a reliable method for identifying insect antioxidant and detoxifying enzyme genes. [23][24][25] Through transcriptome sequencing, some oxidative stress-related genes, such as SOD, POD, and metallothionein, were identified from C. medinalis after C. medinalis granulovirus infection, and these genes were involved in the metabolic process of ROS. 26 A previous transcriptome study on Drosophila melanogaster responses to Steinernema carpocapsae infection indicated that genes associated with stress response and metabolic processes were strongly induced.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RNA sequencing (RNA‐Seq) has been widely used in the study of insect stress response, and this technique has emerged as a reliable method for identifying insect antioxidant and detoxifying enzyme genes 23–25 . Through transcriptome sequencing, some oxidative stress‐related genes, such as SOD , POD , and metallothionein , were identified from C. medinalis after C .…”
Section: Introductionmentioning
confidence: 99%
“…Although chemical treatment is the most effective method to control E. obliqua , growing consumer interest in tea as a healthy beverage and concerns over environmental impact of chemical treatment (Kergunteuil et al., ; Sun et al., ; Yang et al., ) have led to widespread adoption of biological control measures in China to produce safer (contaminant‐free) and organic teas (Li et al., ; Zhang et al., ). Such control measures often involve botanical insecticides, which show low toxicity in mammals and are easily degraded; thus far, a few natural products or plant extracts, such as curcumin, allicin and alkaloids, have shown promising activities against various agricultural pests (Liu et al., ; Luo et al., ).…”
Section: Introductionmentioning
confidence: 99%